Expression of SRP-9001 dystrophin and stabilization of motor function up to 2 years post-treatment with delandistrogene moxeparvovec gene therapy in individuals with Duchenne muscular dystrophy - Mendell, Jerry R.; Shieh, Perry B.; McDonald, Craig M.; Sahenk, Zarife; Lehman, Kelly J.; Lowes, Linda P.; Reash, Natalie F.; Iammarino, Megan A.; Alfano, Lindsay N.; Sabo, Brenna; Woods, Jeremy D.; Skura, Christy L.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Delandistrogene moxeparvovec (SRP-9001) is an investigational gene transfer therapy designed for targeted expression of SRP-9001 dystrophin protein, a shortened dystrophin retaining key functional domains of the wild-type protein. This Phase 2, double-blind, two-part (48 weeks per part) crossover study (SRP-9001-102 [Study 102]; NCT03769116) evaluated delandistrogene moxeparvovec in patients, aged ≥4 to <8 years, with Duchenne muscular dystrophy. Primary endpoints (Part 1) were change from baseline (CFBL) in SRP-9001 dystrophin expression (Week 12), by western blot, and in North Star Ambulatory Assessment (NSAA) score (Week 48). Safety assessments included treatment-related adverse events (TRAEs). Patients were randomized and stratified by age to placebo (n=21) or delandistrogene moxeparvovec (n=20) and crossed over for Part 2. SRP-9001 dystrophin expression was achieved in all patients: mean CFBL to Week 12 was 23.82% and 39.64% normal in Parts 1 and 2, respectively. In Part 1, CFBL to Week 48 in NSAA score (least-squares mean, LSM [standard error]) was +1.7 (0.6) with treatment versus +0.9 (0.6) for placebo; p=0.37. Disparity in baseline motor function between groups likely confounded these results. In 4-to-5-year-olds with matched baseline motor function, CFBL to Week 48 in NSAA scores was significantly different (+2.5 points; p=0.0172); but not significantly different in 6-to-7-year-olds with imbalanced baseline motor function (–0.7 points; p=0.5384). For patients treated with delandistrogene moxeparvovec in Part 2, CFBL to Week 48 in NSAA score was +1.3 (2.7); whereas for those treated in Part 1, NSAA scores were maintained. As all patients in Part 2 were exposed to treatment, results were compared with a propensity-score-weighted external control (EC) cohort. The LSM difference in NSAA score between the Part 2 treated group and EC cohort was statistically significant (+2.0 points; p=0.0009). The most common TRAEs were vomiting, decreased appetite, and nausea. Most occurred within the first 90 days and all resolved. Results indicate robust expression of SRP-9001 dystrophin and overall stabilization in NSAA up to 2 years post-treatment. Differences in NSAA between groups in Part 1 were not significant for the overall population, likely because cohorts were stratified only by age, and other critical prognostic factors were not well matched at baseline.